2022
DOI: 10.1371/journal.pone.0266133
|View full text |Cite
|
Sign up to set email alerts
|

Potential geographic distribution of relict plant Pteroceltis tatarinowii in China under climate change scenarios

Abstract: Pteroceltis tatarinowii (Pteroceltis: Ulmaceae) is a deciduous tree that has a cultivation history of more than 2000 years in China. As an excellent afforestation tree species and rare and endangered tertiary relic plant, P. tatarinowii has high ecological protection value. Due to the forest destruction caused by predatory logging and natural environmental factors, the population of P. tatarinowii in China has decreased significantly. In this study, the potential geographical distribution of P. tatarinowii in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…We further expected ( Hypothesis 2 ) that the distribution range of most of the species would be resilient to climate change. We observed universal northward shifts in agreement with many other empirical studies (Kumar and Rawat 2022; Lu et al 2021; Mueller et al 2022; Yang et al 2022) as well as that the distribution ranges of most species increased in size (Fig. 1).…”
Section: Discussionsupporting
confidence: 92%
“…We further expected ( Hypothesis 2 ) that the distribution range of most of the species would be resilient to climate change. We observed universal northward shifts in agreement with many other empirical studies (Kumar and Rawat 2022; Lu et al 2021; Mueller et al 2022; Yang et al 2022) as well as that the distribution ranges of most species increased in size (Fig. 1).…”
Section: Discussionsupporting
confidence: 92%
“…Climatic variables were obtained from the WorldClim Database (www.worldclim.org) [37]. The data received from WorldClim can be used for mapping and spatial modeling [38][39][40]. Soil variables included soil types from the Resource and Environment Science and Data Center (https://www.resdc.cn/ Default.aspx), soil particle-size distribution dataset [41] and soil quality data from the Harmonized World Soil Database (HWSD) (https://www.fao.org/soils-portal/data-hub/soil-mapsand-databases/harmonized-world-soil-database-v12/en).…”
Section: Environmental Datamentioning
confidence: 99%
“…Although the temperature increment induced by climate change may increase the suitable habitat area of some species [6], for some plant species in special habits it will also reduce the suitable distribution area and may even push the species to the verge of extinction [7,8]. Studies have indicated that species sensitive to climate change often migrate to high-altitude and high-latitude areas under future climate change [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%